1989
DOI: 10.1016/0736-5748(89)90033-6
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evidence for a neurite growth‐promoting activity in trembler mouse serum

Abstract: Basal lamina components, such as heparan sulfate proteoglycan (HSPG) and laminin play an important role in neuritic outgrowth for CNS and PNS neurons in culture. The mutant mouse 'Trembler' is characterized by hypomyelinization and production of an excess of basal lamina layers around Schwann cells in peripheral nerves. In order to analyse whether or not the serum of the mutant animals contains neurite outgrowth-promoting factors, we cultured rat spinal cord neurons in the presence of Trembler serum. Under the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
1993
1993

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…Trembler serum, in contrast with normal mouse serum, contained, as we have previously suggested [19], a powerful mitosis-stimulating activity which rapidly in creased the proportion of dividing Schwann cells.…”
Section: Mitogenic Effect O F Trembler Serummentioning
confidence: 99%
See 1 more Smart Citation
“…Trembler serum, in contrast with normal mouse serum, contained, as we have previously suggested [19], a powerful mitosis-stimulating activity which rapidly in creased the proportion of dividing Schwann cells.…”
Section: Mitogenic Effect O F Trembler Serummentioning
confidence: 99%
“…In a previous paper, we have suggested that the in crease of neurite outgrowth initiated by Trembler serum in embryonic rat spinal cord cultures is enhanced by the stimulation of nonneuronal cells, fibroblasts and mainly glial cells, which multiply initially [19].…”
Section: Introductionmentioning
confidence: 99%